If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 4y) = 4x + 2y (3x * 2 + 4y * 2) = 4x + 2y (6x + 8y) = 4x + 2y Solving 6x + 8y = 4x + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6x + -4x + 8y = 4x + -4x + 2y Combine like terms: 6x + -4x = 2x 2x + 8y = 4x + -4x + 2y Combine like terms: 4x + -4x = 0 2x + 8y = 0 + 2y 2x + 8y = 2y Add '-8y' to each side of the equation. 2x + 8y + -8y = 2y + -8y Combine like terms: 8y + -8y = 0 2x + 0 = 2y + -8y 2x = 2y + -8y Combine like terms: 2y + -8y = -6y 2x = -6y Divide each side by '2'. x = -3y Simplifying x = -3y
| 180-36-x=102 | | (13x-1)= | | 6+-4+-9+7= | | 0-8b=12 | | 4w+5z=6 | | 10x-1=1-4x | | 6y=5x+3 | | 3b+5b=2(2-b)+6(b-2) | | 3x-24=2x+35 | | 1.4x-0.9=33 | | (10x+29)= | | 5(y+4)=-8y-45 | | 6+2=14-x | | 315+15p=450 | | 8x-6-3x=4 | | -x+3y-4z=-15 | | 200p+40p=350+50p | | 14=n+2 | | 6-4t=10 | | 180=4y+(x+2y) | | x=-2y+5z-9 | | t^2+4t-1=t^2+2t+2 | | -2x^2+8x-9=0 | | 2(2k^2+81)-k= | | y=x^3-6x^2+9x+15 | | -1+4x=14+13x | | -4-2x=-5x-16 | | -x^2+4x+32=32 | | 2t+5-6t= | | 5a^2-4a-12= | | 27a=80.73 | | -29-j=0 |